Loss of Corneal Reflex in Children Undergoing Spinal Anesthesia: A Case Series. Issue 1 (1st January 2020) - Holman, Ashlee E.; Puglia, Michael P.
Abstract : Spinal anesthesia is administered for select procedures in the pediatric population and offers a safe alternative to general anesthesia. In this case series, we report loss of corneal and eyelash reflexes in 4 children who underwent spinal anesthesia for lower abdominal procedures. While initially thought to be the result of higher-than-intended spinal anesthesia, the observation that gentle stimulation produced vigorous phonation, orbicularis oculi constriction, and upper extremity movement suggests an alternative mechanism. This finding highlights a potential gap in knowledge related to the effect spinal anesthesia has on brain dynamics in children. Abstract : Supplemental Digital Content is available in the text.